Micro–Positron Emission Tomography/Contrast-Enhanced Computed Tomography Imaging of Orthotopic Pancreatic Tumor–Bearing Mice Using the αβ Integrin Tracer Cu-Labeled Cyclam-RAFT-c(-RGDfK-) - Winn Aung; Zhao-Hui Jin; Takako Furukawa; Michael Claron; Didier Boturyn; Chizuru Sogawa; Atsushi B. Tsuji; Hidekatsu Wakizaka; Toshimitsu Fukumura; Yasuhisa Fujibayashi; Pascal Dumy; Tsuneo Saga (Molecular Imaging)
The purpose of this study was to develop a clinically relevant orthotopic xenotransplantation model of pancreatic cancer and to perform a preclinical evaluation of a new positron emission tomography (PET) imaging probe, 64 Cu-labeled cyclam-RAFT-c(-RGDfK-) 4 peptide ( 64 Cu-RAFT-RGD), using this model. Varying degrees of α v β 3 integrin expression in several human pancreatic cancer cell lines were examined by flow cytometry and Western blotting. The cell line BxPC-3, which is stably transfected with a red fluorescence protein (RFP), was used for surgical orthotopic implantation. Orthotopic xenograft was established in the pancreas of recipient nude mice. An in vivo probe biodistribution and receptor blocking study, preclinical PET imaging coregistered with contrast-enhanced computed tomography (CECT) comparing 64 Cu-RAFT-RGD and 18 F-fluoro-2-deoxy-D-glucose ( 18 F-FDG) accumulation in tumor, postimaging autoradiography, and histologic and immunohistochemical examinations were done. Biodistribution evaluation with a blocking study confirmed that efficient binding of probe to tumor is highly α v β 3 integrin specific. 64 Cu-RAFT-RGD PET combined with CECT provided for precise and easy detection of cancer lesions. Autoradiography, histologic, and immunohistochemical examinations confirmed the accumulation of 64 Cu-RAFT-RGD in tumor versus nontumor tissues. In comparative PET studies, 64 Cu-RAFT-RGD accumulation provided better tumor contrast to background than 18 F-FDG. Our results suggest that 64 Cu-RAFT-RGD PET imaging is potentially applicable for the diagnosis of α v β 3 integrin–expressing pancreatic tumors.